Effect of leucaena and sesbania supplementation on body growth and scrotal circumference of Ethiopian highland sheep and goats fed teff straw basal diet - Kaitho, R.J.; Tegegne, Azage; Umunna, N.N.; Nsahlai, I.V.; Tamminga, S.; Bruchem, J. van; Arts, J.M. (Elsevier, 1998)
The long term effect of supplementation of Leucaena pallida and Sesbania sesban on growth and reproduction performance was determined on 30 male Ethiopian highland sheep and 25 East African goats. Unchopped teff straw (Eragrostis tef) was given ad libitum and supplemented withe ither wheat bran (150 g), Leucaena (200 or 400 g) or Sesbania (200 or 400 g). The animals were blocked (by species) on live weight and scrotal circumference (SC), and randomly assigned within blocks to the five dietary treatments in a randomized complete block design. Animals supplemented with 400 g of the browses had significantly higher (P<0.05) intake of DM and live weight gain than the other treatments. Sheep had significantly higher (P<0.05) teff straw intake than goats (47.3 and 38.7 g kg W-075, respectively). The correlation between SC and body weight was high and significant in goats (r2 = 0.70, P<0.001) and lower in sheep (r2=0.43, P<0.01). Live weight gain and scrotal circumference changes were significantly (P<0.01) different between treatments in both animal species. Supplementation with browses increased faecal nitrogen output and nitrogen retention. The results from this study indicated type and level of supplement variations on the growth and reproductive performance of sheep and goats.